REPRESENTASI NILAI BUDAYA DALAM CERITA RAKYAT KAPUAS HULU KALIMANTAN BARAT - Lenisa; Rini Agustina; Adisti Primi Wulan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the forms and functions of cultural values found in the folktales Medang Pulang and Bukit Ampan from Kapuas Hulu Regency, West Kalimantan, as well as their relevance to Indonesian language learning at the senior high school level. The background of this research is based on the importance of preserving oral literature as an intangible cultural heritage that contains noble values and reflects the worldview of the community. This study employs a literary anthropology approach with a descriptive qualitative method. The data were collected through interviews, recordings, and text documentation, which were then analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that the Medang Pulang and Bukit Ampan folktales contain three main forms of cultural values. First, the cultural value of human relations with God, reflected through prayers, sacrifices, and gratitude to God for the gift of life and safety. Second, the cultural value of human relations with nature, evident in the community’s perspective that views nature as a source of life and ecological balance. Third, the cultural value of human relations with society, reflected through the spirit of mutual cooperation, solidarity, deliberation, and social empathy. In addition, these two folktales are relevant to Indonesian language learning, particularly in the chapter “Exploring Values in Stories Across Time,” as they can serve as a medium for character education, cultural identity reinforcement, and the preservation of local wisdom.